Access To Justice, Moral Distance And Changing Demands On Law - Cotterrell, Roger (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2019)
This paper reflects theoretically on the concept of access to justice – focusing in turn on each of its limbs – the idea of justice and that of access. ‘Justice’ is considered here not philosophically but socio-legally in terms of a spectrum of types of justice-demands made in relation to law. The idea of ‘access’ is analysed by drawing on socio-legal theory concerned with the remoteness of lawmakers from citizens. The aim is to put the concept of access to justice into a wide theoretical context that highlights changing demands on law and new socio-legal conditions – especially those associated with contemporary multiculturalism and the increasingly significant transnational dimensions of law. The paper argues that these demands and conditions make such a wide view timely and necessary. It proposes that an analysis of relations of law and solidarity taken from Durkheimian sociology can help in clarifying the possibilities and limits of state receptiveness to access to justice demands.